Kidney Transplant Outcomes in Patients With Adenine Phosphoribosyltransferase Deficiency. Issue 10 (October 2020) - Runolfsdottir, Hrafnhildur Linnet; Palsson, Runolfur; Agustsdottir, Inger M. Sch.; Indridason, Olafur S.; Li, Jennifer; Dao, Myriam; Knebelmann, Bertrand; Milliner, Dawn S.; Edvardsson, Vidar O.
Abstract : Background: Adenine phosphoribosyltransferase (APRT) deficiency is a rare, hereditary cause of kidney stones and chronic kidney disease (CKD) which is characterized by 2, 8-dihydroxyadenine renal parenchymal crystal deposition. The aim of this study was to examine outcomes of kidney transplantation in APRT deficiency patients. Methods: Included were 13 patients in the APRT Deficiency Registry of the Rare Kidney Stone Consortium, 2 from Westmead Hospital in Sydney, Australia, and 2 from Necker Hospital in Paris, France. The CKD-EPI and CKiD equations were used to calculate glomerular filtration rate estimates. Allograft survival was analyzed employing the Kaplan-Meier method. The Wilcoxon-Mann-Whitney test was used to compare alllograft outcomes according to xanthine oxidoreductase (XOR) inhibitor treatment status at transplantation. Results: Seventeen patients (9 females) received 22 kidney transplants. Age at first transplantation was 47.2 (14.9–67.0) years. Ten patients received XOR inhibitor therapy pretransplant (11 allografts), while 8 patients did not receive such treatment before transplantation (11 allografts). Two-year allograft survival was 91% and 55% in the 2 groups, respectively ( P = 0.16). The median (range) estimated glomerular filtration rate at 2 years posttransplant was 61.3 (24.0–90.0) mL/min/1.73 m 2 when XOR inhibitor therapy was initiated before transplantation, and 16.2 (10.0–39.0) mL/min/1.73 m 2 ( P = 0.009) when such treatment was not administered pretransplant. Conclusions: Kidney allograft outcomes are good in APRT deficiency patients beginning XOR inhibitor therapy pretransplant. Delay in such treatment is a major cause of premature graft loss in these patients. Increased awareness among clinicians is imperative, promoting early diagnosis of APRT deficiency and pharmacotherapy initiation before kidney transplantation.